Correlation between single pre delivery symphysis-fundal height beyond 36 weeks of gestation and birth weight of newborn after delivery - Sultana, Rahima; Rouf, Salma; Shorna, Sharmin Akhter; Akter, Laila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Accurate assessment of fetal weight is important for optimal obstetric management of labouring mothers. Among the methods of fetal weight estimation, symphysis-fundal height (SFH) measurement is inexpensive and non-invasive readily available simple and acceptable procedure of fetal weight estimation. On the other hand, high rate of low birth weight is one of the causes of high perinatal mortality in our country. Objective was to assess fetal birth weight by measuring symphysis-fundal height. Methods: This cross-sectional observational study was conducted in the department of obstetrics and gynaecology, Dhaka Medical College Hospital, Dhaka from July 2017 to June 2018. Total 200 consecutive pregnant women of gestational age more than 36 weeks were selected as per inclusion and exclusion criteria. The fetal birth weight was measured before delivery of the foetus by measuring SFH and using the formula and was compared with actual birth weight. Results: Maximum (35.5%) pregnant mother were in age group 21-25 years followed by 29.5% in 26-30 years, 25.5% in 31-35 years and 9.5% in >35 years age group and mean age was 28.27±4.95 years. Mean weight of new born was 2.81±0.61 kg. Mean symphysis-fundal height 32.76±3.73 cm and maximum (48.5%) pregnant mother had SFH in 35-36 cm group, followed by 30.5% had ≤30 cm and 21.0% had 31-34 cm in this study. New born birth weight had significant positive correlation with symphysis-fundal height. Conclusions: Symphysis-fundal height has significant positive correlation with birth weight of new born.